Biodiesel From Used Cooking Oil Using Nipah (Nyypa Fruticans) Skin Ash As A Heterogene Catalyst By Transesterification Process - Zainuddin Ginting; Meriatna Meriatna; Rizka Mulyawan; Tata Tirani; Asnadia Asnadia; Luthfi Mughni Anisa Haryono (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
One of the consequences of excessive palm oil use is the production of waste palm oil (used cooking oil). To overcome this problem, efforts are needed to convert used cooking oil into more valuable products, such as biodiesel; because of its high fatty acid content, the used cooking oil has considerable potential in developing biodiesel fuel. This research aims to utilize used cooking oil in making biodiesel using heterogeneous catalyst ash derived from Nipah fruit skin calcined at 500 °C for ± 4 hours. Nipah is a type of palm (monocotyledon) that grows in mangrove forest ecosystems, in tidal areas near the seaside, or offshore. The characteristics of parts of Nipah, such as leaves, and skin, chemically contain a lot of cellulose, hemicellulose, and lignin and contain inorganic elements such as Na, K, Cl, Mg, Ca, Si, P, S, and Al. The transesterification process reacts oil with methanol to produce methyl esters and glycerol.  Process variables, namely transesterification reaction time of 60, 90, 120, and 150 minutes, and the mole ratio of methanol to oil of 1:19, 1:21, and 1:23, were observed in this experiment. Biodiesel characteristics were obtained with a density of 860.2 g/mL and a viscosity of 2.37 mm2/s. They contained 44.14% Palmitic acid and 43.04% Octadecenoic acid (oleic), which is to the Indonesian National Standard (SNI). The maximum yield obtained was 93.3598% using a mole ratio of oil: methanol 1:23 at 60°C for 120 minutes, TFT 1:1, and 3% catalyst mass. The results obtained in this study indicate that Nipah fruit skin-based catalysts can be used to produce biodiesel.